(3TQM Ydi GdQSGdI GdYVOjIs - (3GddjKj GdSeQbfOj, CHh GdbGSe Hf CHj HcQ, HYO (B888 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj NU GdGfSGf HeYQaI GhVGY GdcdGe heHGfjg hLYd GdMQha GUhd cdeJg hXQha eYGfjg adeG TGY aj GdCeUGQ GdQSGdI GdYVOjI hcGfJ eTJedI Ydi eSGFd Objb hJMbjbGJ YejbI eY ZGjI GdEjLGR s
(3BNQgG (B:s
(3JTGHg GdMQa aj GdJRGe PcQ GdeJYdb hPdc eKd Phh ahb aEf eaghegeG cdj dCfgeG HeYfi UGMH hYdh hEf cGfG dG jSJYedGf EdG aj LRFjf EVGajjf HGdfSHI Edi eYfGgeG GdPj gh GdUGMH hGdYdh JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\173s
(3cTa GdXfhf (B1\898s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs